2021
DOI: 10.1177/0003134820951456
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Under-triage on Trauma Outcomes in Older Populations ≥65 Years

Abstract: Background Undertriage of older trauma patients is implicated as a cause for outcome disparities. Undertriage is defined by an Injury Severity Score (ISS) ≥16 without full trauma activation. We hypothesized that in patients ≥65 years, undertriage is associated with unfavorable discharge. Methods This is a retrospective study of patients ≥65 years admitted at a Level 1 Trauma Center between July 2016 and June 2018 with blunt trauma. The Matrix method was used to determine the undertriage rate, and outcomes were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 19 publications
1
1
0
Order By: Relevance
“…Permutation-based variable importance showed that age and comorbidities (including hypertension, diabetes mellitus, cerebral infarction, and dementia) contribute to undertriage, which is consistent with the results of previous studies [ 27 , 28 ]. In addition, some chief complaint categories are highly crucial for undertriage.…”
Section: Discussionsupporting
confidence: 90%
“…Permutation-based variable importance showed that age and comorbidities (including hypertension, diabetes mellitus, cerebral infarction, and dementia) contribute to undertriage, which is consistent with the results of previous studies [ 27 , 28 ]. In addition, some chief complaint categories are highly crucial for undertriage.…”
Section: Discussionsupporting
confidence: 90%
“…We found that old age, diabetes mellitus, dementia, and a history of cerebral infarction were associated with undertriage. A previous study conducted at a trauma center showed that age ≥ 65 years [ 19 ], female sex, dementia [ 20 ], history of cerebral infarction, and heart failure [ 21 ] were risk factors for undertriage of trauma patients. Among these risk factors for undertriage of trauma patients, old age, dementia, and history of stroke were also identified as risk factors in our study.…”
Section: Discussionmentioning
confidence: 99%